Magnetic, dielectric and complex impedance spectroscopic studies of nanocrystalline Cr substituted Li-ferrite - Hankare, P. P.; Patil, R. P.; Sankpal, U. B.; Garadkar, K. M.; Sasikala, R.; Tripathi, A. K.; Mulla, Imtiaz S. (Journal of Magnetism and Magnetic Materials, 2010)
Nanocrystalline Li0.5Fe2.5-xCrxO4 (2.5 <= x >= 0) ferrites were prepared by a sol-gel autocombustion route. X-ray diffraction was employed to confirm the cubic spinel phase formation of the ferrites. The lattice parameter decreases with increase in Cr content. The saturation magnetization, coercivity and remanance were studied as a function of Cr content. The dielectric constant and dielectric loss were measured as a function of frequency in the frequency range 20 Hz-1 MHz. Frequency dependence of dielectric constant shows dielectric dispersion due to the Maxwell-Wagner type of interfacial polarization. In order to understand the conduction mechanism, complex impedance measurements were carried out. The substitution of chromium plays an important role in changing the dielectric and magnetic properties of lithium ferrites. (C) 2010 Published by Elsevier B.V.
Keywords: Complex impedance; dielectric response; Ferrites; Magnetic hysteresis; Sol-gel synthesis; X-ray diffraction

Synthesis and characterization of nanocrystalline zinc substituted nickel ferrites - Hankare, P. P.; Sankpal, U. B.; Patil, R. P.; Mulla, Imtiaz S.; Sasikala, R.; Tripathi, A. K.; Garadkar, K. M. (Journal of Alloys and Compounds, 2010)
Nanocrystalline zinc substituted nickel ferrites, Ni(1-x)Zn(x)Fe(2)O(4) (0.0 <= x <= 1.0) have been prepared by citrate gel auto-combustion method. The effect of zinc ion content on structural, electrical transport and magnetic properties has been studied. The X-ray diffraction (XRD) pattern revealed that, all the compositions possess single-phase spinel structure. The nano-sized grain structure formation was confirmed by transmission electron microscopy (TEM). The dc electrical resistivity shows the samples are semiconducting in nature. The magnetic measurements showed that the composition Ni(0.6)Zn(0.4)Fe(2)O(4) has maximum saturation magnetization (M(s)) while high coersivity (Hc) for ZnFe(2)O(4). Thermoelectric power measurement study showed that the compounds, with x <= 0.4 are p-type and for x > 0.4 behaves n-type conduction mechanism. (C) 2010 Published by Elsevier B.V.
Keywords: Electron microscopy; Magnetic; Sintering; X-ray diffraction